Pengaruh Psikologi Latihan Terhadap Pembinaan Olahraga dan Sport Personology Atlet Club Bolavoli TWOSRA - Novita Chandra Devi; Indardi, Nanang (Faculty of Sport and Health Sciences, 2022)
The purpose of this study was to determine the effect of exercise psychology on sports coaching & sport personology of volleyball athletes. This study uses quantitative methods in the form of experiments with the type of Pre-Experimental Design. The population used in this study amounted to 24 people & used a sampling technique in the form of purposive sampling. The sample in this study amounted to 14 people with the condition that the sample was a TWOSRA volleyball club athlete aged 13-17 years. The data in this study were obtained from a questionnaire & test stages which were divided into 2 parts (pre-test & post-test) & then processed using IBM Statistic SPSS series 25. This study has passed ethical clearance by the Health Research Ethics Commission (KEPK) State University of Semarang. . The results of this study indicate that the average value of the volleyball technique pre-test is 74,786 & the post-test results of volleyball technique get an average value of 104.786. For the results of the questionnaire, the t-count value of the three research variables, namely exercise psychology (x), sports coaching (Y1) & sport personology (Y2) is more than t table, so it can be concluded that exercise psychology affects sports coaching & athlete sports personology. TWOSRA volleyball club, Sragen Regency. For further research, it is expected to discuss the influence of exercise psychology on athlete achievement & discuss the evaluation of the results of the application of sports psychology.